A retrospective audit of the first screening round of the Maltese breast screening programme. Issue 1 (February 2017) - Mizzi, D.; Zarb, F.; Dennis, A.
Abstract: Purpose: To analyse whether the screening performance parameters of the Maltese National Breast Screening Programme first screening round met requirements set by European standards. The association between screening age and results of screening performance parameters was also investigated. Method: Quantitative methodology was used to review examinations of women who were recalled for a technical recall or further assessment rates. All accessible members of the population recalled during the first round were retrospectively reviewed resulting in a sample of 2300 recalled examinations. Results: Malta's first screening round met the European Guidelines recommendations for technical repeat rate (0.26%), early recall rate (0.45%), breast cancer detection rate (13.77 per 1000 women) and Positive Predictive Value of screening test (7.58%). However, local recall rate (18.53%) and further assessment rate (18.27%) were higher than recommended. The Chi square test showed a statistically significant difference (p ≤ 0.05) in recall rates between the compared age groups, as younger women (51–55 years) were more likely to have a negative diagnosis after the initial mammogram whereas older women (56–60 years) were more likely to be recalled. There was no age discrepancy (p ≥ 0.05) in local breast cancer detection rate and positive predictive value of screening test. Conclusion: Although the Maltese first screening round performed well, this study found deficiencies in recall and further assessment rates, which according to literature may result in psychological morbidity and inefficient use of screening resources. This study also concluded that when a cohort is analysed, age is not as significant as the screening round itself (first/subsequent). Highlights: The Maltese technical and early recall rates complied with European guidelines. Breast cancer detection rate and positive predictive value conformed to guidelines. The recall and further assessment rates exceeded recommended European guidelines. Effect of age on screening parameters is not as significant as the screening round.